The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/bf03168230
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de los nucleótidos CMP y UMP en la fatiga en ratas

Abstract: The aetiology of muscle fatigue has yet not been clearly established. Administration of two nucleotides, cytosine monophosphate (CMP) and uridine monophosphate (UMP), has been prescribed for the treatment of neuromuscular affections in humans. Patients treated with CMP/UMP recover from altered neurological functions and experience pain relief, thus the interest to investigate the possible effect of the drug on exhausting exercise. With such aim, we have determined, in exercised rats treated with CMP/UMP, exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Error bars correspond to the standard error of the means. These nucleotides have been shown to be important in energy metabolism, based on metabolic parameters measured in muscle, blood serum, and liver (i.e., levels of lactate, glucose, and several metabolic enzymes) during exercise in rats treated with CMP/UMP [24]. Seven of these 17 metabolites appeared in the bioactivity network for both males and females (Supplemental Data, Figures S3 and S4, respectively).…”
Section: Impacts Of Effluent Exposures On Metabolic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Error bars correspond to the standard error of the means. These nucleotides have been shown to be important in energy metabolism, based on metabolic parameters measured in muscle, blood serum, and liver (i.e., levels of lactate, glucose, and several metabolic enzymes) during exercise in rats treated with CMP/UMP [24]. Seven of these 17 metabolites appeared in the bioactivity network for both males and females (Supplemental Data, Figures S3 and S4, respectively).…”
Section: Impacts Of Effluent Exposures On Metabolic Pathwaysmentioning
confidence: 99%
“…Specifically, both metabolites, which are involved in pyrimidine metabolism, were significantly up-regulated at the 100% effluent level for both sexes, but only CMP was significantly up-regulated at the 20% level, and only in the female fish. These nucleotides have been shown to be important in energy metabolism, based on metabolic parameters measured in muscle, blood serum, and liver (i.e., levels of lactate, glucose, and several metabolic enzymes) during exercise in rats treated with CMP/UMP [24]. Other metabolite changes included fructose-6-phosphate (F6P; 260.0296 amu), sedoheptulose-7phosphate (S7P; 290.0402 amu), and uridine diphosphate glucose (UDP-Glc; 566.0565 amu), which were up-regulated to some degree in all exposure groups, and significantly so in the 100% effluent in both sexes.…”
Section: Impacts Of Effluent Exposures On Metabolic Pathwaysmentioning
confidence: 99%
“…Regarding peripheral nervous system, studies in vivo have shown that the addition of these nucleotides favors the regeneration of myelinatednerve fibers following crush injury to the sciatic nerve of the rat, thus accelerating the process of nerve repair [12], improving recovery after exhaustive exercise [18] and inhibiting spinal pain transmission [19].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the beneficial effects of nucleotides on the central nervous system. Oral administration of UMP alone or in combination with unsaturated fatty acids increases spine density and the synthesis of synaptic proteins and ameliorates the impairment of hippocampal-dependent memory in impoverished rats, which provides a rationale for testing these compounds in the search for a way to treat neurological diseases characterized by synaptic loss [18,[20][21][22]. Moreover, UTP administration to rats protects against cerebral ischemia reperfusion injury by reducing the infarct zone [26].…”
Section: Introductionmentioning
confidence: 99%
“…Своєчасна діагностика ушкоджень гілок трійчастого нерва при переломах важлива ще і тому, що травматичний неврит є однією з причин порушення репаративной регенерації. Встановлено, що ушкодження трійчастого нерва викликає ряд функціональних і морфологічних змін в тканинах обличчя, органах порожнини рота [12][13][14]. Дана проблема збереження та відновлення нерва після травми досі зберігає свою актуальність.…”
unclassified